Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s10646-012-0877-4
|View full text |Cite
|
Sign up to set email alerts
|

Individual-based model of Chironomus riparius population dynamics over several generations to explore adaptation following exposure to uranium-spiked sediments

Abstract: Natural populations are chronically exposed to various pollutants over many generations. It is thus crucial to understand and quantify adaptive dynamics of stressed populations in order to increase the relevance of ecotoxicological risk assessment. However, long-term consequences to population exposure are not much studied yet. The present study investigated evolutionary responses of Chironomus riparius populations exposed to uranium (heavy metal pollutant) and to assess the underlying mechanisms. To fulfil ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Moreover, they showed a similar trend in growth reduction for exposed organisms and for unexposed organisms originated from adult males and females exposed to uranium during their immature life stages. Beaudouin et al (2012) showed effects of uranium on both growth and reproduction of Chironomus riparius and also showed that exposure to uranium during eight generations led to a phenotypic selection via a differential survival characterized by longer time to emergence and smaller larval maximal size. They estimated a longterm No Effect Concentration (NEC) of 28.3 µg g −1 dry weight of sediment.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, they showed a similar trend in growth reduction for exposed organisms and for unexposed organisms originated from adult males and females exposed to uranium during their immature life stages. Beaudouin et al (2012) showed effects of uranium on both growth and reproduction of Chironomus riparius and also showed that exposure to uranium during eight generations led to a phenotypic selection via a differential survival characterized by longer time to emergence and smaller larval maximal size. They estimated a longterm No Effect Concentration (NEC) of 28.3 µg g −1 dry weight of sediment.…”
Section: Discussionmentioning
confidence: 97%
“…For this, the DEB model of G. aculeatus will be combined with an individual‐based model. DEB‐IBM models have already used to others species and have demonstrated their abilities to extrapolate from ecotoxicological data measured on organisms in laboratory conditions to biological endpoints convenient (Beaudouin et al., , ; Martin et al., ). Moreover, data on population obtained in our mesocosm (De Kermoysan et al., ) could be used to improve the DEB model by giving information on the energy budget in male after maturity and during the reproduction season.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical models are increasingly used in ecological risk assessment, due to the rise in demand for ecological realism in regulatory risk assessment (Forbes et al., ). Models are conveniently used to upscale from individual level to population level (Beaudouin, Dias, Bonzom, & Péry, ; Beaudouin et al., ; Goussen et al., ; Martin et al., ). However, their development requires a large amount of data on the life cycle of the organisms (Beaudouin et al., ; Goussen et al., ; Péry, Ducrot, Mons, & Garric, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DEB modelling can also be adapted to other types of analysis. Thereby, individual based model (IBM) based on DEB modelling can permit to analyse population level data, especially multi-generation studies (Beaudouin et al, 2012;Martin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%